BOLSA FAMILIA DALAM KERANGKA WELFARE STATE: SOLUSI KESEJAHTERAAN ATAU KEBIJAKAN MINIMALIS DI BRASIL - Zahra Hanifah Salma; Bella Ola Shakira; Shandy Gupa Pratama; Jerry Indrawan; Reja Reja (Universitas Sunan Drajat Lamongan, Indonesia, 2026)
This study aims to analyze the Bolsa Família Program within the welfare state framework to determine whether it is more appropriately understood as a welfare solution or merely a minimalist social policy in Brazil. The study is motivated by persistent poverty and social inequality, which have prompted the government to strengthen social protection policies. This research employs a qualitative approach using a literature review of books, scholarly journals, policy documents, and reports from international organizations. The analysis is conducted using the welfare state concept and John Rawls' Theory of Justice. The findings indicate that Bolsa Família has not only contributed to reducing poverty but has also improved access to education, healthcare, and social protection for low-income households through the Conditional Cash Transfer (CCT) mechanism. From Rawls' perspective, the program reflects the implementation of the *difference principle* by directing redistributive benefits to the least advantaged while promoting *fair equality of opportunity* through expanded access to education and healthcare. Nevertheless, the program still faces limitations in addressing structural inequality and fostering long-term social mobility, particularly in transforming deeply rooted patterns of social and economic inequality across generations. This study concludes that Bolsa Família is better understood as a welfare instrument within the welfare state framework rather than merely a minimalist policy, as it demonstrates the state's long-term commitment to providing sustainable social protection for vulnerable groups while promoting greater social justice and more equitable opportunities.